Pendidikan Akhlak Anak dalam Perspektif Imam Al-Ghazali - Syamsul Bahri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
This study looks at the concept of children's moral education through the eyes of Imam al-children, Ghazali's with the goal of discovering the concept of moral education via the eyes of Imam al-children. Ghazali's The data analysis method used in the writing is content analysis, which is a sort of library research. Documentation is the method of data collecting, with primary data being Ihya' 'Ulumuddin's book and secondary data being books and scholarly papers pertinent to the theme. The study's findings show that having positive attitudes, ethics, and morals when seeking knowledge is the best method to achieve educational goals. Because morals and ethics are essential in the pursuit of knowledge. As a result, that information became valuable and a blessing. There are ten points in Ghazali's concept of moral education for youngsters.